Relationship Between Age and Depth of Invasion and Histopathological Features in Colorectal Cancer Patients in the Anatomical Pathology Department of Cut Meutia General Hospital (RSUCM) 2018 - 2021 - Mulyati Sri Rahayu; Khairunnisa Z; Nabil Ibnu Sina (PT FORMOSA CENDEKIA GLOBAL, 2023)
Colorectal cancer has become one of the most common and most diagnosed cancers in the world, with as many as 1.4 million new cases being discovered each year. This cancer affects many elderly patients, but not a few young patients also experience it. Depth of invasion and type of histopathological appearance are the determining factors in determining the prognosis of colorectal cancer. The purpose of this study was to determine the relationship between age and depth of invasion and histopathological features in patients with colorectal carcinoma in the anatomical pathology section of RSU Cut Meutia, North Aceh for the 2018-2021 period. This research is a retrospective analytic study using the approach cross sectional study and use data taken from the results of laboratory examinations. Anatomical Pathology during the 2018-2021 period. The results of the study found that cancer that had invaded the subserosa to the peri-colorectal tissue (T3) and invaded other organs and/or perforated visceral peritoneum (T4) had a higher percentage in the age group.≤54 years, but statistically no significant relationship was found. Description adenocarcinoma is the most common histopathological appearance and has a higher percentage in the age group≤54 years, but statistically no significant relationship was found. So it can be concluded that there is no significant relationship between age and depth of invasion and the histopathological appearance of colorectal cancer patients